1981
DOI: 10.2172/5593138
|View full text |Cite
|
Sign up to set email alerts
|

Tube vibration in industrial size test heat exchanger (30/sup 0/ triangular layout - six crosspass configuration)

Abstract: 18 RMS acceleration versus flowrate; (a) Tuhs TJ-19 (V), (b) Tube U-21 (0), (c) Tube V-20 (A), (d) Tube U-5 (0); Open symbolincreasing flow, solid symboldecreasing flow 48 19 Frequency response curves; %be V-20 20 RMS acceleration versus flowrate; Tube U-21 (0) , Tube V-20 (A), Tube U-5 (0) 5 1 LIST OF FIGURES (Contd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This type of dynamic response behavior, viz., a gradual increase to large amplitude motion, is not uncommon, especially with dense fluids, and has been observed in laboratory tests [4]. However, as discussed in an earlier report [2], it does make definition of a critical flowrate more difficult as there is no abrupt increase in response to positively identify the threshold.…”
Section: Cmentioning
confidence: 87%
See 3 more Smart Citations
“…This type of dynamic response behavior, viz., a gradual increase to large amplitude motion, is not uncommon, especially with dense fluids, and has been observed in laboratory tests [4]. However, as discussed in an earlier report [2], it does make definition of a critical flowrate more difficult as there is no abrupt increase in response to positively identify the threshold.…”
Section: Cmentioning
confidence: 87%
“…Test Procedure/Data Processing For the sake of completeness some of the discussion presented on this topic in the previous test reports [1,2] is repeated here. It is practically not possible to instrument all of the more than 400 tubes in the bundle, or even the somewhat smaller number of tubes in the window regions that will b more susceptible to vibration by virtue of their lower natural frequencies.…”
Section: Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Wambsganss et al [13] observed that, for the industrial size shell-and-tube exchanger used in their tests, the primary contribution to the vibration response was in the frequency range from 10 to 80 Hz; it was also observed that tube response associated with fluidelastic instability typically occurred in the frequency range of 20 to 30 Hz.…”
Section: A Tube Motionmentioning
confidence: 99%